Regeneration of soil fertility in relationship with the diversification of rubber agroforestry systems - Tongkaemkaew, Uraiwan; Commons, Michael; Verhofste, Robbe; Lin Phooi, Chooi; Wonglom, Prisana; Bua-Khwan, Benchawan (Thaksin University, 2025)
Rubber agroforestry is an agricultural system that integrates rubber trees with other compatible crops or trees to optimize land use, improve soil fertility, and enhance biodiversity. This study compares the soil richness of Rubber Agroforestry (RF) plantations with varying species diversity and Rubber Monoculture (RM) plantations. The research was conducted in Phatthalung Province, Thailand, a region with a long history of rubber agroforestry, though some areas are cultivated as rubber monocultures. Soil samples were collected at 0–15 cm and 15–30 cm depths and analyzed for physical characteristics, organic matter content, and nutrient composition. The findings indicate that soil quality is influenced by plantation type, soil depth, and locality. RM and RF plantations exhibit differences in soil physical properties, cation exchange capacity (CEC), organic carbon (OM), total nitrogen, phosphorus, potassium, calcium, and magnesium content. Across all parameters studied, except phosphorus, RF plantations demonstrated higher soil fertility indicators than RM plantations. Additionally, the NDVI analysis from 2017 to 2023 showed that RF plantations had a plant cover of 63%, compared to 58% in RM plantations. The higher plant density in RF plantations contributed to organic matter accumulation, thereby enhancing soil fertility. Conclusion: The study highlights that rubber agroforestry practices contribute to increased soil nutrient levels and organic matter content, underscoring their potential benefits for sustainable land management.